Teaching methodologies in Mathematics in relation to pupils mathematical achievement: basis for a proposed training program - Montero, Corazon Z. (Parañaque City: Olivarez College, 2008)
This study sought to examine the teaching methodologies of Mathematics in relation to the pupil's mathematical achievement as basis for a proposed training program. The descriptive method with documentary analysis was used and the instrument adapted is a questionnaire composed of four parts. The statistical treatment used was percentage, weighted mean, the SPEARMAN RHO and ANOVA. The study involved 50 pupils and 6 matnematics teachers in the Elementary Department for the school year 2006- 2007. This study airmed to detemine the relationship of pupils achievement to the teaching methodologies used in teaching Mathematics by the elementary teachers at Olivarez College which served as basis for a proposed training program.
Master Thesis